Glucocorticoid receptor and androgen receptor-targeting therapy in patients with castration-resistant prostate cancer - Pak, Sahyun; Suh, Jungyo; Park, Seo Young; Kim, Yunlim; Cho, Yong Mee; Ahn, Hanjong (Frontiers in Oncology, 2022)
Objective: The glucocorticoid receptor (GR) promotes resistance to androgen receptor (AR)-targeting therapies in castration-resistant prostate cancer (CRPC) by bypassing AR blockade. However, the clinical relevance of evaluating GR expression in patients with CRPC has not been determined. The present study investigated the association of relative GR expression in CRPC tissue samples with treatment response to AR-targeting therapy. Methods: Levels of GR, AR-FL, and AR-V7 mRNAs were measured in prostate cancer tissue from prospectively enrolled CRPC patients who were starting treatment. Patients were divided into groups with high and low AR-V7/AR-FL ratios and with high and low GR/AR-FL ratios. The primary endpoint was prostate-specific antigen (PSA) response rate to treatment. Results: Evaluation of 38 patients treated with AR-targeting therapies showed that the PSA response rate was significantly higher in patients with low than high AR-V7/AR-FL ratios (77.8% vs. 25.0%, p=0.003) and in patients with low than high GR/AR-FL ratios (81.3% vs. 27.3%, p=0.003). Patients with low GR/AR-FL ratios had higher rates of PSA progression-free survival (46.0% vs. 22.4%, p=0.006), radiologic progression-free survival (28.9% vs. 10.0%, p=0.02), and overall survival (75.2% vs. 48.0%, p=0.037) than patients with high GR/AR-FL ratios. The association of GR/AR-FL ratio with PSA response to AR-targeting therapy remained significant in multivariable models. Conclusion: Relative GR expression is associated with sensitivity to AR-targeting therapy and survival in patients with CRPC. Large-scale prospective validation and liquid biopsy-based studies are warranted.